Forward Trajectory of a Positive Black Self - Nolan Stevens (The Thinker)
It is said that the future of black art is bright. The truth is the future of blackness in any context can only ever be promising. The past fails to provide a representative depository of positive black excellence. It is with this in mind that the present and more specifically the future are the only spaces were blackness can hope to aspire for more. Simply put, positivity connected to blackness can only ever truly exist as a futuristic endeavour. The Asisebenze Art Atelier (AAA) artist studio and dealership is an apt case study f or this argument.